2015
DOI: 10.1073/pnas.1511870112
|View full text |Cite
|
Sign up to set email alerts
|

Transition to farming more likely for small, conservative groups with property rights, but increased productivity is not essential

Abstract: Theories for the origins of agriculture are still debated, with a range of different explanations offered. Computational models can be used to test these theories and explore new hypotheses; Bowles and Choi [Bowles S, Choi J-K (2013) Proc Natl Acad Sci USA 110(22): [8830][8831][8832][8833][8834][8835] have developed one such model. Their model shows the coevolution of farming and farming-friendly property rights, and by including climate variability, replicates the timings for the emergence of these events see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…farming could be readily explained if early farming were more productive than foraging, estimates suggest that this may not have been the case 2 and alternative hypotheses based on environmental, social, and demographic parameters have been proposed 13,14 .…”
mentioning
confidence: 99%
“…farming could be readily explained if early farming were more productive than foraging, estimates suggest that this may not have been the case 2 and alternative hypotheses based on environmental, social, and demographic parameters have been proposed 13,14 .…”
mentioning
confidence: 99%
“…It has been suggested that a general idea of land ownership emerged along with agriculture (e.g. North and Thomas, 1977;Earle, 2004;Zeder, 2011;Bowles and Choi, 2013;Gallagher, Shennan and Thomas, 2015). However, although groups of people during the Neolithic probably claimed right to territories, expressed by monuments such as megaliths and grave mounds (e.g.…”
Section: Settlements and Land Ownershipmentioning
confidence: 99%
“…Evidence for intensive iron-working possibly pre-dating the Mossi states is known from central Burkina Faso, 50 and settlement patterns similar to those found today in Gulmance society (dispersed household compounds) developed in the Gobnangou on the southern edge of the Gulmance region in the early second millennium CE. 51 Similar to northern Burkina Faso, several areas experienced population reductions and/or site abandonments in the 14th-15th centuries CE, a phenomenon that has been attributed to diverse causes such as increasing aridity, plague epidemics and/or political developments. 52…”
Section: Central West African Savannamentioning
confidence: 99%